Electron and photon induced processes in SF5CF3 - Limão-Vieira, P. (2010)
﻿The photo-absorption cross section of trifluoromethyl sulphur pentafluoride, SF5CF3 has been measured using synchrotron radiation in the range of 4–11 eV (310 nm > l > 110 nm) and comparison made with electron energy loss spectroscopy (EELS). The measured VUV cross sections are used to derive the photolysis rate of SF5CF3 in the terrestrial atmosphere. It is estimated that the lifetime for this molecule is the order of a 1000 years and the calculated global warming potential (GWP) is found to be between 17000 and 18100, making it one of the most potent global warming gases in the terrestrial atmosphere.